Effects of premedication with Melatonin and L-Theanine on Ketamine induced anesthesia in New Zealand White Rabbits - Nasiroleslami, Mohammadreza; Mohitmafi, Soroush (Archives of Advances in Biosciences, 2015)
Melatonin, a pineal gland secreted hormone has different effects on mammalian physiology. Recently, specific receptors of melatonine have been found in the central nervous system and spinal cord of rabbits. L - Theanine is a unique amino acid in the tea plant (Camellia sinensis). The effects of this amino acid is based on increasing GABA and dopamine levels in the brain and has a weak effect on the NMDA receptors, receptors that inhibitory effects of ketamine on them have been proven. The aim of this study was to evaluate the effect of oral combination of melatonin and L-Theanine on analgesia and anesthesia characteristics, induced by intramuscular injection of ketamine hydrochloride in New Zealand white rabbits. Five rabbits were anesthetized by intramascular injection of 35 mg/kg of 10% ketamine hydrochloride (Control group). The same rabbits, after 2 weeks, and complete clearance of the drugs from their bodies, were administered orally with the combination of 25 mg L-Theanine and 3 mg melatonin, 60 min prior to ketamine injection (Experimental group). In both groups, time spending to induction of anesthesia, duration of anesthesia, anesthetic depth and vital signs including rectal temperature, heart rate, respiratory rate, SPO2 and palpebral, pedal and righting reflexes were observed. The results showed no significant differences in onset of anesthesia, duration of anesthesia and anesthetic depth, heart rate, respiratory rate, body temperature and oxygen saturation of hemoglobin. As a conclusion, administration of 3 mg melatonin and 25 mg L-theanine could not effect on ketamine hydrochloride anesthesia in New Zealand white rabbits.